Tindak Pidana Kesusilaan dalam KUHP 2023: Perspektif Kelompok Agama Minoritas - Nella Sumika Putri (Badan Strategi Kebijakan Hukum, 2025)
Indonesia, a nation celebrated for its rich diversity of ethnicities and religions, embodies a societal pluralism that deeply influences perceptions of morality and acceptable behaviour. The enactment of the 2023 Criminal Code reflects these complexities, particularly in its use of